988. Overcoming Prescriber Concerns through Successful Access and Affordability of PrEP. (31st December 2020) - Whelchel, Kristen; Zuckerman, Autumn; DeClercq, Josh; Choi, Leena; Rashid, Shahristan; Kelly, Sean
Abstract: Background: Increasing the number of human immunodeficiency virus (HIV) pre-exposure prophylaxis (PrEP) providers expands PrEP access to more eligible patients and aids in ending the HIV epidemic. Non-prescribers of PrEP have noted perceived financial barriers as a limitation to prescribing. The purpose of this study is to describe the PrEP medication access process and outcomes in patients seen at a multidisciplinary PrEP clinic. Methods: We conducted a single-center, retrospective, cohort study of patients prescribed PrEP with emtricitabine-tenofovir disoproxil fumarate from a multidisciplinary clinic with prescriptions filled by Vanderbilt Specialty Pharmacy between 9/1/2016 and 3/31/2019. Patient data were gathered from the electronic health records and pharmacy claims data. We evaluated three different time periods: patient initial evaluation to PrEP initiation, prescription of PrEP to insurance approval, and PrEP insurance approval to initiation. Treatment initiation was considered a delay of > 7 days from initial evaluation, and reasons for delay were recorded. Continuous variables are presented as median (interquartile range, IQR) and categorical variables are presented as percentages. Results: Characteristics of the 63 included patients are in Table 1; most were male (97%), white (84.%), commercially insured (94%) with a median age of 38 years (IQR 29—47). The primary indication for PrEP was men who have sex with men at high risk for acquiring HIV (97%). The median time from initial appointment to treatment initiation was 7 days (IQR 4—8); Figure 1. Treatment delays were observed in 25% of patients and were mostly driven by patient preference (50% of delays). Insurance prior authorization was required in 27% of patients, all of which were approved. Median total out of pocket medication costs for the entire study period were 0 (IQR 0 – 0); Figure 2. Most patients (86%) used a manufacturer copay card. Table 1 Patient Characteristics Figure 1 Time to Treatment Initiation Figure 2 Patient Out of Pocket Cost and Savings Conclusion: In our cohort of mostly commercially insured men, the majority were able to access PrEP with low out of pocket costs facilitated by manufacturer assistance. Though generalizability beyond this population is limited, these results contradict perceived financial barriers to PrEP access. Disclosures: All Authors : No reported disclosures